Knowledge, attitude, practice, and generation of electronic waste (e-waste) among students of health sciences in a private college in Pune - Kshtriya, Pranav S; Anchala, Raghupathy (Indian Journal of Community Health, 2023)
Background: In "the era of information," e-waste is a major threat to solid waste management and public health. E-waste contains dangerous and destructive compounds that may affect the environment and human health if not properly handled. The objective of the study was to assess the knowledge, attitude, practice on e-waste and to determine e-waste generation rates for two electronic products: computers and cell (mobile) phones among health science students of the Symbiosis Institute of Health Sciences, Pune. Methodology: A web-based and institution-based cross-sectional study of students pursuing different health science courses was conducted. Out of 680 students, 405 were randomly selected, dispersed in six strata, and the Google questionnaire was disseminated using a proportionate probability to size ratio, with 188 participants responding at a 46.41% response rate. Results: Out of 188 respondents, 95 (50.6%) and 77 (41.2%) study subjects knew about the health and environmental risks associated with e-waste. Physical damage caused 126 (67%) of the research participants to replace their electronics. 67% would learn about e-waste management if it were on the course. 66% purchase 1-3 electronics devices every year, while 23% purchase 4-6. Overall e-waste generation rates among the participants were 0.223 units/capita/year for computers and 0.42 units/capita/year for mobile phones. Conclusion: This research reveals a lack of understanding and behaviours related to e-waste among students of health sciences, highlighting the need for health education on e-waste for public health and awareness on safe e-waste disposal, both of which are critical for a risk-free future.